Development of Quantitative and Temporal Scalar Implicatures in a Felicity Judgment Task - Schaeken, Walter; Schouten, Bojoura; Dieussaert, Kristien (Frontiers in Psychology, 2019)
Experimental investigations into children’s interpretation of scalar terms show that children have difficulties with scalar implicatures in tasks. In contrast with adults, they are for instance not able deriving the pragmatic interpretation that “some” means “not all” (Noveck , 2001; Papafragou & Musolino, 2003). However, there is also substantial experimental evidence that children are not incapable of drawing scalar inferences and that they are aware of the pragmatic potential of scalar expressions. In these kinds of studies, the prime interest is to discover what conditions facilitate implicature production for children. One of the factors that seem to be difficult for children is the generation of the scalar alternative. In a Felicity Judgment Task (FJT) the alternative is given. Participants are presented with a pair of utterances and were asked to choose the most felicitous description. In such a task, even five-year-old children showed a very good performance (Chierchia et al., 2001; Foppolo, Guasti, & Chierchia, 2012). Our study wants to build on this tradition, by using a FJT where not only “some-all” choices are given, but also “some-many” and “many-all”. We compared performance of 59 five-year-old children with 34 11-year-old children. The results indicated that performance of both age-groups was clearly above chance. With respect to the ‘some-all’ choice, we find in both age-groups very high accuracy, replicating Foppolo et al. (2012). However, for the five-year-old children, the critical and ambiguous items were more difficult than the control items and they also performed worse on these two items than the eleven-year-old children. Interestingly with respect to the issue of scalar diversity, the eleven-year-old children were also presented temporal items, which turned out to be more difficult than the quantitative ones.